2022
DOI: 10.3389/fphys.2022.856507
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Macular Structural and Microcirculatory Characteristics of Posterior Staphyloma in High Myopic Eyes by Swept Source Optical Coherence Tomography Angiography

Abstract: Purpose: To investigate the characteristics of macular structures and microcirculation of posterior staphyloma (PS) and explored factors related to PS in eyes with high myopia.Methods: There were 114 eyes of 82 patients in this study. Using 1:1 matching of the axial length of myopic eyes, patients were divided into no PS (NPS) and PS groups. Comprehensive ophthalmic examinations were performed on all patients. Structural parameters were acquired using swept source optical coherence tomography (SS-OCT). OCT ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…PST was negatively correlated with optic disc tilt, PPA area, and optic disc vascular density (0–2 mm) and positively correlated with mean PST. Previous studies have revealed that subfoveal scleral thickness is negatively correlated with age and axial length, and positively correlated with subfoveal choroidal thickness [ 30 , 31 ]. We arrived at similar conclusions in the PST study.…”
Section: Discussionmentioning
confidence: 99%
“…PST was negatively correlated with optic disc tilt, PPA area, and optic disc vascular density (0–2 mm) and positively correlated with mean PST. Previous studies have revealed that subfoveal scleral thickness is negatively correlated with age and axial length, and positively correlated with subfoveal choroidal thickness [ 30 , 31 ]. We arrived at similar conclusions in the PST study.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to mechanical stretching caused by the limited bulge, subfoveal CT significantly decreased in the PS group [ 3 , 16 ]. However, our study showed that in adults with axial length ≥ 26 mm, a significant reduction was only observed in the superior thickness in the PS subgroup compared with that in group 1.…”
Section: Discussionmentioning
confidence: 99%
“…Thinning of the choroid in eyes with PS mainly appears in the small vascular layer, followed by the medium blood vessel [ 15 ]. The subfoveal and parafoveal choroidal capillary perfusion areas in eyes with PS are smaller than those in no posterior staphyloma eyes [ 16 ]. Moreover, these changes may be involved in the formation of neovascularization and myopic maculopathy in eyes with PS [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…OCT and OCTA measurements were obtained about 1 h after cycloplegia to eliminate the potential confounding effects of accommodation on choroidal thickness and blood perfusion 13 . To minimise the potential confounding effects of diurnal variation, all measurements were conducted between 12:00 and 15:00 h. The SS‐OCT/OCTA system (VG200S; SVision Imaging, http://intalight.com) was used to assess the macular structures and vascular characteristics with high resolution and reproducibility 14,15 . The device was equipped with an SS laser and an eye‐tracking mechanism to eliminate eye movement artefacts.…”
Section: Methodsmentioning
confidence: 99%
“…com) was used to assess the macular structures and vascular characteristics with high resolution and reproducibility. 14,15 The device was equipped with an SS laser and an eye-tracking mechanism to eliminate eye movement artefacts. The central wavelength of the swept-source (SS) laser was 1050 nm (full width range, 990-1100 nm) with a scan rate of 200,000 A-scans per second.…”
Section: Swept-source Oct (Ss-oct)/octa Image Acquisitionmentioning
confidence: 99%